Addresses of hospitals in Paris (note)
C02-0034-001 I.C.3. TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From To Department. Date SUBJECT. Gillies & T.U.C. (France) 1. Maison des Blesses 4, Cite Monthiers, Paris (9e) 2. Centrale Sanitaire Internationale 38 Rue de Chateaudun, Paris (9e) 292C/946/2/34